Progress toward integrating Distress as the Sixth Vital Sign: a global snapshot of triumphs and tribulations in precision supportive care. Issue 1 (July 2019) - Fradgley, Elizabeth A.; Bultz, Barry D.; Kelly, Brian J.; Loscalzo, Matthew J.; Grassi, Luigi; Sitaram, Brindha
Abstract: Background: The International Psycho-Oncology Society (IPOS) recognizes psychosocial cancer care as a universal human right. IPOS emphasized that distress should be measured as the 6th Vital Sign alongside temperature, blood pressure, pulse, respiratory rate, and pain. To date, >75 cancer care organizations and accreditation bodies have endorsed screening, monitoring, and treating the multifactorial symptoms of distress as an essential component to high-quality care. The degree to which this international commitment has translated into the integration of precision supportive care within clinical settings is unknown. Methods: Building upon a 2018 IPOS World Congress Symposium, this commentary provides 4 snapshots into the progress made toward integrating precision supportive care in India, Australia, Europe, and the United States. The commentary demonstrates the different approaches taken to develop screening practices or overcome barriers to comprehensive precision supportive care. Results: Although psychosocial cancer care is a universal right, service and patient barriers to implementation remain, such as: inadequate workforce distribution and service investment in psychosocial care; siloed teams and limited communication skills; and cultural challenges. Recurrent themes emerged which can be used to invigorate commitment to IPOS standards: ongoing capacity building of the international psycho-oncology community; supporting communication skills training and encouraging programmatic thinking within services; and advocating for ongoing investment in precision supportive care through evaluation and strong clinical leadership. Conclusions: In examining 4 unique settings, the commentary recognizes the geographic variation in health care resources and social contexts of cancer care alongside cultural perspectives on psychosocial distress, screening methods, and the value of precision supportive care.